CHARACTERISTICS OF PRACTICAL ACTIVITY IN ECOLOGICAL RELATIONSHIP TO NATURE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article studies the specific features of practical activities in the ecological attitude of a person to nature. The article highlights the ecological attitude of people to nature, and therefore, together with it, ecological education, ecological behavior - manifestations of behavior towards nature and the environment. Ecological attitude is formed not only through practical actions, but also through the perception of nature as a value. The social significance, educational and cultural role, adaptability to local conditions, the need for continuity and result-orientedness of the ecological attitude to nature are highlighted with examples.